Answer:
\sqrt(3)[cos((4\pi )/(45))+isin((4\pi )/(45))]
Step-by-step explanation:
The first one.
Answer:
![g(3x-2) = (3x-2)^{2}](https://tex.z-dn.net/?f=g%283x-2%29%20%3D%20%283x-2%29%5E%7B2%7D)
Step-by-step explanation:
![g(x)=x^{2}](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E%7B2%7D)
To do this, you must substitute
for x in the equation g(x)
![g(3x-2) = (3x-2)^{2}](https://tex.z-dn.net/?f=g%283x-2%29%20%3D%20%283x-2%29%5E%7B2%7D)
Simplified this would be
![9x^{2} -12x+4](https://tex.z-dn.net/?f=9x%5E%7B2%7D%20-12x%2B4)
Use the Pythagorean theorem:
x = √(12.7^2 - 6.2^2)
x = √(161.29 - 38.44)
x = √122.85
x = 11.08
Round to 11.1 m